Concrete materials : series 1 - Adnan, Suraya Hani (Penerbit UTHM, 2017)
This book provides the various usages of materials for producing good concrete. It will appeal to several major audiences. It is a compilation of works which using different types of material in concrete. There have been researches, literatures, methodologies and results that reveal the materials act in concrete. Some guidelines and suggestion also have been included for improving the utilization of the materials. It is expected that the skills of concrete produced will be enhanced by more exploration in experimental experiences.